Do Large TARGET2 Balances Bear Risks for the Euro Area? - Maximilian J. Horst; Ulrike Neyer (Credit and Capital Markets – Kredit und Kapital, 2022)
Large increases in TARGET2 balances in the euro area since 2008 have led to concern and debate about the appropriate interpretation and policy reaction~– in particular in TARGET2 creditor countries such as Germany. Against this background, we examine the main drivers of the increases and asymmetries in TARGET2 balances that have emerged in the context of the financial and sovereign debt crises as well as in the context of the Eurosystem's implementation of quantitative easing (QE) and the COVID-19 pandemic. Moreover, this paper analyzes the potential risks for euro area member states in the case of (i) the unchanged continuity of the monetary union, (ii) the withdrawal of a member state with (large) TARGET2 liabilities, and (iii) the break-up of the whole monetary union. Depending on the outcome of exit negotiations and the operational handling, there can be direct risks in the form of default losses of TARGET2 balances and indirect risks in the form of threat potentials if TARGET2 debtor countries pretend to plan to leave the euro area. Based on this, we discuss adaption options for the TARGET2 payment system and consider an exit from the ECB's accommodative monetary policy in order to scale back the high amount of excess liquidity in the euro area banking sector which is the prerequisite for the emergence of TARGET2 balances.
Keywords: F45; E42; E52; E58; 330; TARGET2 Balances; Payment System; Euro Area; Central Bank Balance Sheet; Monetary Policy; Quantitative Easing (QE); Excess Liquidit